fMRI Prediction of Naming Change after Adult Temporal Lobe Epilepsy Surgery: Activation Matters - You, Xiaozhen (Epilepsia, 2019)
OBJECTIVE: We aimed to predict language deficits after epilepsy surgery. In addition to evaluating surgical factors previously examined, we determined the impact of the extent of fMRI activation resected on naming ability. METHOD: Thirty-five adults (mean age 37.5+/−10.9 yr, 13 males) with temporal lobe epilepsy completed a pre-operative fMRI auditory description decision task, which reliably activates frontal and temporal language networks. Patients underwent temporal lobe resections (20 left). The Boston Naming Test (BNT) was used to determine language functioning before and after surgery. Language dominance was determined for Broca’s and Wernicke’s area (WA) by calculating a laterality index following SPM processing. We used an innovative method to generate anatomical resection masks automatically from pre- and post-operative MRI tissue map comparison. This mask provided 1) resection volume; 2) overlap between resection and pre-operative activation; 3) overlap between resection and WA. We examined post-operative language change predictors using stepwise linear regression. Predictors included parameters described above as well as age of seizure onset (AOS), pre-operative BNT score, resection side and its relationship to language dominance. RESULTS: Seven out of thirty-five adults had significant naming decline (six dominant-side resections). The final regression model predicted 38% of the naming score change variance (adjusted r(2)=0.28, p=0.012). The percentage of top 10% fMRI activation resected (p=0.017) was the most significant contributor. Other factors in the model included WA LI, AOS, volume of WA resected, WA LI absolute value (extent of laterality). SIGNIFICANCE: Resection of fMRI activation during a word definition decision task is an important factor for post-operative change in naming ability, along with other previously reported predictors. Currently, many centers establish language dominance using fMRI. Our results suggest the amount of the top 10% of language fMRI activation in the intended resection area provides additional predictive power and should be considered when planning surgical resection.